Yo-Yo Intermitten Recovery Test: A study of football players’ VO2max physical condition - Suryadi, Didi; Yanti, Novi; Tjahyanto, Teddy; Ramli; Rianto, Louis (UIR Press, 2023)
The Yo-Yo Intermittent Recovery Test is frequently used to evaluate VO2max and is crucial for determining an athlete's physical condition. However, its effectiveness in accurately assessing the physical condition of football players remains limited. This study aims to analyze the level of the physical condition of football players' VO2max which will be used as evaluation material for designing training programs so that the pattern of coaching becomes focused and produces achievements. This research used a quantitative approach to the survey method. The subjects of this study were Pusaka FC football club athletes, the sampling technique used total sampling so that all athletes were a sample of 23 players. The test instrument used the Yo-Yo Intermitten Recovery Test level 2. Data analysis used descriptive percentages, with the assistanceof the Microsoft Excel 2019 software application. The results of the study show that the VO2max level value in soccer athletes is 13.04% of athletes in the poor category and 34.78% in the good category. Below average, 47.82% shows the average category, and there is only 4.35%, which shows the value of the good category. Based on the results of the VO2max ability test, the average classification of Club Pusaka FC players is still relatively low. However, it is necessary to know that the limitations of this study lie in the condition of the players' nutritional intake which has not been controlled and their age which must also be taken into consideration by researchers. Furthermore, it can find information on the effect of athlete nutrition on endurance ability.